Effects of squeeze-off on mechanical properties of polyethylene pipes - Zhang, Yi; Jar, P.-Y. Ben (International journal of solids and structures, 2018)
Squeeze-off is a common practice in industry to shut off or reduce gas flow in polyethylene (PE) pipe. In this study, influence of squeeze-off on degradation of mechanical properties for PE pipe was examined. Three squeezing speeds of 0.01, 1 and 50 mm/min were used to cover the possible squeeze-off scenarios that may be encountered during the pipe repair or maintenance. Results show that squeeze-off of PE pipe causes significant degradation in elastic modulus and yield strength, with the maximum reduction of 82% for elastic modulus and 27% for yield strength. Furthermore, contradictory to the common belief that slower is better, reducing the squeezing speed was found to have no effect on the extent of property degradation. In view of those findings, a study was conducted using mechanical testing and finite element (FE) simulation to elucidate the damage evolution in PE pipe in different loading modes (including tension and compression) and with different loading history (in terms of maximum pre-strain level and loading speed). Results show that both tensile and compressive loading modes can cause severe degradation in elastic modulus and yield strength. The results also show that under a single loading mode, the extent of damage at a given pre-strain level is indeed a function of loading rate. However, in a pipe which has been squeezed to subject the pipe wall to a combined tensile and compressive stresses, degradation of the “apparent” elastic modulus and yield strength, defined as their equivalent values for a given wall thickness, becomes insensitive to the loading rate.